Նախագծային աշխատանքը՝ որպես սովորողների ճանաչողական կարողությունների զարգացման միջոց - Հակոբյան, Գրետա; Քերոբյան, Սոֆյա
Հոդվածում քննարկված են նախագծային ուսուցման տեսական-գործնական հարցեր։ Հիմնավորված է նախագծային ուսուցման կարևորությունը 21-րդ դարի հմտությունների և սովորողների կարողունակությունների ձևավորման չափորոշչային պահանջների շրջանակներում։ Վերլուծված են նախագծային ուսուցման նպատակները, սկզբունքները, իրականացման ձևերը, ուսուցչի գործառույթները։ Նկարագրված է Կոտայքի մարզի Բալահովտի միջնակարգ դպրոցում իրականացված նախագծային աշխատանքի օրինակ։ Բնութագրված են աշխատանքի բովանդակությունը, ընթացքը, քայլաշարը, հիմնական ուղղությունները, վերջնարդյունքները։ Педагогика участия и сотрудничества актуальна для всех уровней образования, а также для всех образовательных учреждений. Сегодня одним из важнейших вопросов образования является перенос знаний в жизнь. С этой точки зрения весьма оправдана и актуальна организация работы по методу проектов․ В данной статье рассматриваются теоретичиские и практические вопросы проектного обучения. Анализированы цели, принципы, формы реализации проектного обучения. Сделана попытка классифицировать типы проектной работы, сформулировать определение учебной проектной работы, указать ее особенности, детализировать роль и функции педагога в процессе проектной работы. Обоснована важность проектного обучения в рамках стандартных требований формирования компетенции учащихся 21-го века. Описан пример проектной работы, проведённый в Балаовитской средней школе Котайкского марза. Описаны также содержание, процесс, алгоритм действии, основные направления и конечные результаты данной проектной работы. Утверждается, что проектное обучение, как образовательная технология, предполагает интеграцию психолого-педагогических, предметных и методических знаний учащихся. Participatory and cooperative pedagogies are relevant to all levels of education, as well as to all educational settings. Today one of the most important issues of education is the transfer of knowledge to life. From this point of view, the organization of works in the field of education through the project method is highly justified. Theoretical and practical issues are considered in the article. The goals of project learning, ways of implementation are analyzed. We have tried to classify project works with a certain logic formulate, the definition of educational project work, point out its features, specify the role and functions of the teacher. There is also justified the importance of project-based learning of the 21st century skills within the framework of standard requirements for students' compitence formation. An example of project work implemented in Balahovit secondary School is described in detail. The content, process and structure of the work are characterized. The main points and final results are also indicated. It is justified that as a educational technology, planned learning implies the integration of learner' psychological, pedagogical, subject and methodical knowledge. Conclusions: project-based learning contributes to the development of the ability to set cognitive goals and find alternative ways of their implementation, ensures the formation of information culture, the development of communication skills, flexibility, independence and uniqueness of thinking. The result of the implementation of the project method, which helps to identify the interrelations of the elements of the logic of scientific research, is the development of creative cognitive abilities.
Keywords: Մանկավարժություն